Evidence for chemokine synergy during neutrophil migration in ARDS. Issue 1 (5th August 2016) - Williams, Andrew E; José, Ricardo J; Mercer, Paul F; Brealey, David; Parekh, Dhruv; Thickett, David R; O'Kane, Cecelia; McAuley, Danny F; Chambers, Rachel C
Abstract : Background: Acute respiratory distress syndrome (ARDS) is a life-threatening condition characterised by pulmonary oedema, respiratory failure and severe inflammation. ARDS is further characterised by the recruitment of neutrophils into the lung interstitium and alveolar space. Objectives: The factors that regulate neutrophil infiltration into the inflamed lung and our understanding of the pathomechanisms in ARDS remain incomplete. This study aimed at determining the role of the chemokine (C-C motif) ligand (CCL)2 and CCL7 in ARDS. Methods: CCL2 and CCL7 protein levels were measured in bronchoalveolar lavage (BAL) fluid obtained from lipopolysaccharide(LPS)-challenged human volunteers and two separate cohorts of patients with ARDS. Neutrophil chemotaxis to ARDS BAL fluid was evaluated and the contribution of each was assessed and compared with chemokine (C-X-C motif) ligand 8 (CXCL8). Chemokine receptor expression on neutrophils from blood or BAL fluid of patients with ARDS was analysed by flow cytometry. Results: CCL2 and CCL7 were significantly elevated in BAL fluid recovered from LPS-challenged volunteers and patients with ARDS. BAL fluid from patients with ARDS was highly chemotactic for human neutrophils and neutralising either CCL2 or CCL7 attenuated the neutrophil chemotactic response. Moreover, CCL2 and CCL7 synergised with CXCL8 to promote neutrophil migration. Furthermore, neutrophils isolated from the blood or BAL fluid differentially regulated the cell surface expression of chemokine (C-X-C motif) receptor 1 and C-C chemokine receptor type 2 during ARDS. Conclusion: This study highlights important inflammatory chemokines involved in regulating neutrophil migration, which may have potential value as therapeutic targets for the treatment of ARDS.